USE OF AN INDIRECT ENZYME-LINKED IMMUNOSORBENT ASSAY (ELISA) TO DETECT ANTIBODIES IN AYU (Plecogiossus altivelis) VACCINATED BY IMMERSION ADMINISTRATION - Sukenda, .; Wakabayashi, Hisatsugu (Indonesian Society of Scientific Aquaculture (ISSA), 2002)
ABSTRACTAn indirect enzyme-linked immunosorbent assay (ELISA) was used to detect serum antibody in ayu, Plecoglossus altivelis, immunized against Pseudomonasplecoglossicida by immersion vaccination. First, the procedure of the ELISA was optimized and the sensitivity was checked. Secondly, the formalin-killed cells (FKC) of P. plecoglossicida was administered to ayu by immersion vaccination. Two weeks after vaccination, fish were divided into two groups, one group was given booster. The level of specific antibody production of both boostered and vaccinated only fish were statistically higher than unvaccinated control fish at the time of each blood collection. However, the differences between the boostered and vaccinated only fish were not statistically significant.Keywords : immunization, Pseudomonas plecoglossicida, ayu, ELISA ABSTRAKIndirect enzyme-linked immunosorbent assay (ELISA) digunakan untuk mendeteksi antibodi pada ayu, Plecoglossus altivelis, yang diimunisasi dengan cara perendaman untuk melawan infeksi Pseudomonas plecoglossicida. Pertama, prosedur ELISA dioptimasikan dan sensitivitas dari metode ini juga diperiksa. Kemudian, bakteri Plecoglossus altivelis yang sudah dimatikan dengan formalin diberikan ke ikan ayu dengan vaksinasi perendaman. Dua minggu setelah vaksinasi, ikan dibagi menjadi dua kelompok, satu kelompok diberi vaksinasi kedua. Produksi antibodi spesifik dari ikan-ikan yang divaksinasi satu kali dengan vaksinasi dua kaii secara statistik lebih tinggi dibandingkan dengan control. Akan tetapi, tidak ada perbedaan produksi antibodi antara ikan yarig divaksanisi satu kali dengan divaksinasi dua kali.Kata kunci : imunisasi, Pseudomonasplecoglossicida, ayu, ELISA